Space and time under persecution : the German-Jewish experience in the Third Reich - Miron, Gai; Watzman, Haim; University of Chicago Press (Chicago : London : University of Chicago Press, 2023)
"The rapid and radical transformations of the Nazi Era challenged the ways German Jews experienced space and time, two of the most fundamental characteristics of human existence. In Space and Time under Persecution, Guy Miron documents how German Jews came to terms with the harsh challenges of persecution-from social exclusion, economic decline, and relocation to confiscation of their homes, forced labor, and deportation to death in the east-by rethinking their experiences in spatial and temporal terms. Miron first explores the strategies and practices German Jews used to accommodate their shrinking access to public space, in turn reinventing traditional Jewish space and ideas of home. He then turns to how German Jews redesigned the annual calendar, came to terms with the ever-growing need to wait for nearly everything, and developed new interpretations of the past. Miron's insightful analysis reveals how these tactics expressed both the continuous attachment of Jews to key elements of German bourgeois life as well as their struggle to maintain Jewish agency and express Jewish defiance under Nazi persecution"--
Space: Public Space -- Jewish Places and Spaces -- At Home -- Time: The Circle of Time -- The Flow of Time -- Turning toward the Past.
Includes bibliographical references and index.